(untitled) (Experimental biology, 2015)
mTOR is a protein kinase belongs to the family of phosphoinositide-3-kinase (PI3K)-related kinases (PIKKs). mTOR exists in two distinct complexes called complex 1 (mTORC1) and complex 2 (mTORC2). Due to their different protein compositions, the mTOR complexes have important differences in their sensitivities to rapamycin, in the upstream signals they integrate, in the substrates they regulate, and in the biological processes they control. Cell growth and proliferation are orchestrated by signaling networks in response to environmental cues such as nutrients, growth factors, hormones, intracellular and extracellular energy status, and stress conditions. mTOR signaling pathway is a central regulator in a diverse array of vital cellular processes, including proliferation, growth, differentiation, and survival. TOR (target of rapamycin) protein kinase is an evolutionarily conserved regulator in these signaling networks. Because of the mTOR is linked to the PI3K/PTEN/Akt/TSC signaling pathway, it is the main cause for development of a wide variety of cancers and other diseases.